Bart’s Syndrome. - Tiwari, Manish; Saple, Pallavi; Khamkar, Anilkumar; Ambekar, Pranju (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
We present a case of a newborn with congenital absence of skin in both feet, dystrophic nails in both the lower limbs and who shortly after birth developed bullae and erosions in hands, ears, buttocks and mouth. With these findings, the diagnosis of Bart syndrome was made. Bart syndrome is a clinical diagnosis characterized by triad of the localized absence of the skin present at birth, epidermolysis bullosa (EB), lesions of the mouth and mucosa, and disfigured nails. Combination of absence of skin i.e. aplasia cutis congenita (ACC) and with simplex, junctional, or dystrophic types of epidermolysis bullosa (EB) is classified as type six ACC which is a very rare clinical condition and very few cases are available in literature and this case is fifth from India.